Effects of human relaxin on orthodontic tooth movement and periodontal ligaments in rats - Madan, Monica S. (2007)
INTRODUCTION: The rate-limiting step in orthodontic treatment is often the rapidity with which teeth move. Using biological agents to modify the rate of tooth movement has been shown to be effective in animals. Relaxin is a hormone present in both males and females. Its main action is to increase the turnover of fibrous connective tissues. Thus, relaxin might increase the amount and rate of tooth movement through its effect on the periodontal ligament (PDL). The purpose of this study was to measure the effect of relaxin on orthodontic tooth movement and PDL structures. METHODS: Bilateral orthodontic appliances designed to tip maxillary molars mesially with a force of 40 cN were placed in 96 rats. At day 0, the animals were randomized to either relaxin or vehicle treatment. Twelve rats in each group were killed at 2, 4, 7, and 9 days after appliance activation. Cephalograms were taken at appliance placement and when the rats were killed. Tooth movement was measured cephalometrically in relation to palatal implants. Fractal analysis and visual analog scale assessments were used to evaluate the effect of relaxin on PDL fiber organization at the tension sites in histologic sections. The in-vitro testing for PDL mechanical strength and tooth mobility was performed by using tissue from an additional 20 rats that had previously received the same relaxin or vehicle treatments for 1 or 3 days (n = 5). RESULTS: Both groups had statistically significant tooth movement as functions of time. However, relaxin did not stimulate significantly greater or more rapid tooth movement. Fractal and visual analog scale analyses implied that relaxin reduced PDL fiber organization. In-vitro mechanical testing and tooth mobility assessments indicated that the PDL of the mandibular incisors in the relaxin-treated rats had reduced yield load, strain, and stiffness. Moreover, the range of tooth mobility of the maxillary first molars increased to 130% to 170%, over vehicle-treated rats at day 1. CONCLUSIONS: Human relaxin does not accelerate orthodontic tooth movement in rats; it can reduce the level of PDL organization, reduce PDL mechanical strength, and increase tooth mobility at early time points.